Blood levels of stable nitric oxide metabolites in metabolic syndrome and diabetes mellitus - Zulaykho Muralimzhanovna Shamansurova (Endocrinology Research Centre, 2009)
Aim. To measure stable metabolites of nitric oxide (SMNO), i.e. nitrites and nitrates, and compare the results with other biochemical characteristicsof blood in patients with type 1 and 2 diabetes mellitus (DM1 and DM2) or metabolic syndrome (MS). Materials and methods. The following parameters were measured in 61 patients with DM, 12 with obesity, 8 with impaired glucose tolerance (IGT),and 12 healthy subjects: blood glucose level (fasting and 2 hr postprandially), HbA1c, insulin, C-peptide, SMNO, lipid spectrum, erythrocyte sialidaseactivity (ESA), and insulin resistance index (HOMA). Results. Postprandial glycemia was elevated in DM1, DM2, and IGT patients, HOMA in those with DM2 and IGT, ESA in all DM and MS patients.SMNO level was reduced in all groups especially in patients with DM and diabetic nephropathy. It negatively correlated with total cholesterol, TG,LDL, and ESA. Conclusion. Blood SMNO level as an indicator of endothelial dysfunction is of high diagnostic value starting from the early stages of impaired carbohydratemetabolism.